A highly flame-retardant honeycomb composite material and its preparation method and application

By using powdered activated carbon and modified cystic algae powder and other components to prepare high flame retardant honeycomb composites, the problems of insufficient mechanical strength and poor high temperature resistance in high temperature VOCs gas treatment are solved, and the adsorption performance of the material is improved and the high temperature flame retardant performance is met.

CN117019120BActive Publication Date: 2025-03-21TIANJIN UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311170401.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-09-12
Publication Date
2025-03-21
Estimated Expiration
2043-09-12

AI Technical Summary

Technical Problem

The existing honeycomb adsorbent materials have problems such as insufficient mechanical strength and poor high temperature resistance when dealing with high-temperature VOCs gas, which cannot meet the current safety production requirements.

Method used

High flame retardant honeycomb composite materials are prepared by powdered activated carbon, modified cysteine ​​powder, phytic acid, binder, silicon nitride, sodium chloride and water. The adsorption and high-temperature resistance of the material are improved by calcining the modified cysteine ​​powder, extrusion molding, drying and activation steps.

Benefits of technology

It improves the adsorption performance and overall strength of composite materials, extends the service life, and provides good flame retardant performance under high temperature conditions, meeting the requirements of safe production.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention belongs to the technical field of functional materials, and provides a highly flame-retardant honeycomb composite material, a preparation method and an application thereof. The composite material comprises the following components in parts by weight: 40 to 50 parts of powdered activated carbon, 20 to 30 parts of modified black spore algae powder, 1 to 10 parts of phytic acid, 1 to 10 parts of a binder, 1 to 5 parts of silicon nitride, 1 to 5 parts of sodium chloride, and 1 to 10 parts of water. The use of modified black spore algae powder in the present invention not only improves the adsorption of the composite material, but also improves the overall strength of the composite material, thereby extending the service life. The use of phytic acid and silicon nitride greatly improves the flame retardant properties of the composite material, so that the performance of the composite material meets the current safety production requirements.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of functional materials, and in particular to a highly flame-retardant honeycomb composite material and a preparation method and application thereof. Background Art

[0002] VOCs (volatile organic compounds) generally refer to organic compounds with a boiling point between 50 and 260°C at normal pressure, a saturated vapor pressure of more than 134 Pa at room temperature, and strong volatility. The adsorption method has the advantages of high treatment efficiency, simple operation, and stable operation, and is widely used to treat various types of VOCs gases.

[0003] The most commonly used adsorbent for adsorption is activated carbon, especially honeycomb activated carbon, which has been widely used in the treatment of various VOCs gases in recent years, and can achieve a treatment effect of 90% or even higher. Honeycomb activated carbon integrates the characteristics of activated carbon such as high specific surface area, acid and alkali resistance, controllable pore structure, and regeneration after failure, as well as the advantages of high honeycomb structure opening rate, large geometric surface area, wear resistance, and strong resistance to dust pollution. Compared with other types of activated carbon, the biggest advantage of honeycomb activated carbon is its small pressure loss. However, the VOCs gas emitted by many industries is currently at a high temperature, and a large amount of heat will be released during the adsorption and purification of VOCs gas by adsorption, which requires the adsorbent to have a certain high temperature resistance under the premise of ensuring adsorption performance. However, the current honeycomb activated carbon does not have high temperature resistance and does not meet today's safety production requirements.

[0004] Therefore, how to provide a honeycomb composite material with high flame retardancy has become an urgent problem to be solved by those skilled in the art. Summary of the invention

[0005] In view of this, the present invention provides a highly flame-retardant honeycomb composite material and its preparation method and application, which aims to solve the technical problems of the existing honeycomb adsorption materials such as insufficient mechanical strength and poor high temperature resistance.

[0006] In order to achieve the above object, the present invention adopts the following technical solution:

[0007] The present invention provides a highly flame-retardant honeycomb composite material, comprising the following components in parts by weight:

[0008] 40-50 parts of powdered activated carbon, 20-30 parts of modified black spore algae powder, 1-10 parts of phytic acid, 1-10 parts of binder, 1-5 parts of silicon nitride, 1-5 parts of sodium chloride, and 1-10 parts of water.

[0009] Furthermore, the particle size of the powdered activated carbon is ≤100 μm.

[0010] Furthermore, the particle size of the black spore algae powder is 30 to 100 meshes.

[0011] Furthermore, the binder is one or more of starch, dextrin, tar and polyvinyl alcohol.

[0012] Furthermore, the powdered activated carbon is coal-based activated carbon and / or fruit shell activated carbon.

[0013] The present invention also provides a method for preparing the above-mentioned highly flame-retardant honeycomb composite material, comprising the following steps:

[0014] S1, calcining the black spore algae powder to obtain modified black spore algae powder;

[0015] S2, mixing all the raw materials to form a mud material, and extruding it to obtain a honeycomb composite material embryo;

[0016] S3, drying and activating the honeycomb composite material embryo in sequence to obtain a highly flame-retardant honeycomb composite material.

[0017] Furthermore, in the step S1, the calcination temperature is 700-1000° C., and the calcination time is 30-60 min.

[0018] Furthermore, in step S2, the vacuum degree during extrusion is -0.05 to -0.1 MPa.

[0019] Furthermore, in step S3, the drying temperature is 100-200° C., and the drying time is 1-10 hours; the activation temperature is 500-600° C., and the activation time is 1-5 hours.

[0020] The present invention also provides the use of the above-mentioned highly flame-retardant honeycomb composite material in the adsorption and purification treatment of VOCs waste gas.

[0021] It can be seen from the above technical solution that compared with the prior art, the beneficial effects of the present invention are as follows:

[0022] In the present invention, the black spore algae powder is calcined to increase its surface area and adsorption characteristics, thereby indirectly improving the adsorption of the composite material. The calcined black spore algae powder is used in the composite material, which can also improve the overall strength of the composite material, thereby extending the service life;

[0023] The phytic acid used in the present invention will release phosphoric acid and water when decomposed at high temperature (>900° C.). The phosphate groups in the phosphoric acid can form salts with metal ions in the sodium chloride to form a protective layer at high temperature to prevent combustion.

[0024] In the present invention, the use of silicon nitride further enhances the high temperature resistance of the composite material. DETAILED DESCRIPTION

[0025] The present invention provides a highly flame-retardant honeycomb composite material, comprising the following components in parts by weight:

[0026] 40-50 parts of powdered activated carbon, 20-30 parts of modified black spore algae powder, 1-10 parts of phytic acid, 1-10 parts of binder, 1-5 parts of silicon nitride, 1-5 parts of sodium chloride, and 1-10 parts of water.

[0027] In the present invention, the amount of powdered activated carbon used is preferably 42 to 48 parts, more preferably 44 to 46 parts.

[0028] In the present invention, the amount of the modified Nigrosporium powder is preferably 22 to 28 parts, and more preferably 24 to 26 parts.

[0029] In the present invention, the amount of phytic acid used is preferably 2 to 8 parts, more preferably 4 to 6 parts.

[0030] In the present invention, the amount of the binder used is preferably 2 to 8 parts, more preferably 4 to 6 parts.

[0031] In the present invention, the amount of silicon nitride used is preferably 2 to 4 parts, more preferably 3 parts.

[0032] In the present invention, the amount of sodium chloride used is preferably 2 to 4 parts, more preferably 3 parts.

[0033] In the present invention, the amount of water used is preferably 2 to 8 parts, more preferably 4 to 6 parts.

[0034] In the present invention, the particle size of the powdered activated carbon is ≤100 μm, preferably ≤80 μm, and more preferably ≤60 μm.

[0035] In the present invention, the particle size of the black spore algae powder is 30 to 100 meshes, preferably 40 to 80 meshes, and more preferably 50 to 60 meshes.

[0036] In the present invention, the binder is one or more of starch, dextrin, tar and polyvinyl alcohol, preferably one or more of starch, tar and polyvinyl alcohol, and more preferably starch.

[0037] In the present invention, the powdered activated carbon is coal-based activated carbon and / or fruit shell activated carbon, preferably fruit shell activated carbon.

[0038] The present invention also provides a method for preparing the above-mentioned highly flame-retardant honeycomb composite material, comprising the following steps:

[0039] S1, calcining the black spore algae powder to obtain modified black spore algae powder;

[0040] S2, mixing all the raw materials to form a mud material, and extruding it to obtain a honeycomb composite material embryo;

[0041] S3, drying and activating the honeycomb composite material embryo in sequence to obtain a highly flame-retardant honeycomb composite material.

[0042] In the present invention, in step S1, the calcination temperature is 700-1000°C, preferably 800-900°C, and more preferably 850°C; the calcination time is 30-60 min, preferably 40-50 min, and more preferably 45 min.

[0043] In the present invention, in step S2, the vacuum degree during extrusion is -0.05 to -0.1 MPa, preferably -0.06 to -0.09 MPa, and more preferably -0.07 to -0.08 MPa.

[0044] In the present invention, in step S3, the drying temperature is 100-200°C, preferably 120-180°C, and more preferably 140-160°C; the drying time is 1-10h, preferably 2-8h, and more preferably 4-6h; the activation temperature is 500-600°C, preferably 520-580°C, and more preferably 540-560°C; the activation time is 1-5h, preferably 2-4h, and more preferably 3h.

[0045] The present invention also provides the use of the above-mentioned highly flame-retardant honeycomb composite material in the adsorption and purification treatment of VOCs waste gas.

[0046] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0047] Example 1

[0048] The raw materials and dosage used in this embodiment are as follows:

[0049] 45 parts of powdered activated carbon, 24 parts of modified black spore algae powder, 5 parts of phytic acid, 5 parts of starch, 4 parts of silicon nitride, 5 parts of sodium chloride, and 7 parts of water.

[0050] The black spore algae powder is calcined at 850°C for 50 minutes to obtain modified black spore algae powder; then all the raw materials are mixed and stirred in a kneader to form a mud material, the mud material is loaded into a vacuum extruder, and extruded at -0.07MPa to obtain a honeycomb composite material embryo; the honeycomb composite material embryo is dried at 150°C for 5 hours, and then activated at 550°C for 2 hours to obtain a highly flame retardant honeycomb composite material.

[0051] Example 2

[0052] The raw materials and dosage used in this embodiment are as follows:

[0053] 44 parts of powdered activated carbon, 26 parts of modified black spore algae powder, 3 parts of phytic acid, 4 parts of polyvinyl alcohol, 5 parts of silicon nitride, 3 parts of sodium chloride, and 8 parts of water.

[0054] The black spore algae powder is calcined at 900°C for 40 minutes to obtain modified black spore algae powder; then all the raw materials are mixed and stirred in a kneader to form a mud material, the mud material is loaded into a vacuum extruder, and extruded at -0.05MPa to obtain a honeycomb composite material embryo; the honeycomb composite material embryo is dried at 160°C for 4 hours, and then activated at 560°C for 3 hours to obtain a highly flame retardant honeycomb composite material.

[0055] Example 3

[0056] The raw materials and dosage used in this embodiment are as follows:

[0057] 46 parts of powdered activated carbon, 22 parts of modified black spore algae powder, 7 parts of phytic acid, 6 parts of tar, 2 parts of silicon nitride, 3 parts of sodium chloride, and 5 parts of water.

[0058] The black spore algae powder is calcined at 750°C for 30 minutes to obtain modified black spore algae powder; then all the raw materials are mixed and stirred in a kneader to form a mud material, the mud material is loaded into a vacuum extruder, and extruded at -0.09MPa to obtain a honeycomb composite material embryo; the honeycomb composite material embryo is dried at 120°C for 8 hours, and then activated at 580°C for 4 hours to obtain a highly flame retardant honeycomb composite material.

[0059] Comparative Example 1

[0060] Same as Example 1, except that phytic acid was not added.

[0061] Comparative Example 2

[0062] The same as Example 1, except that no black spore algae powder was added.

[0063] Comparative Example 3

[0064] The same as Example 1, except that silicon nitride is not added.

[0065] Performance Testing

[0066] The specific surface area of ​​the material was tested using a high-performance specific surface and micropore analyzer; then a mixture of toluene and air was used as the simulated exhaust gas, with a toluene concentration of 500 ppm and the rest being air. The adsorption performance of the sample for toluene was tested under the condition of an air velocity of 20000 mL / (g·h). The test results are shown in Table 1.

[0067] Table 1 Adsorption performance test results of Examples 1 to 3 and Comparative Examples 1 to 3

[0068] Test items Adsorption rate of toluene Positive pressure compressive strength (MPa) <![CDATA[Specific surface area (m 2 / g)]]> Example 1 98% 14.2 1080 Example 2 94% 13.8 1024 Example 3 96% 13.7 1036 Comparative Example 1 92% 12.6 879 Comparative Example 2 75% 6.6 564 Comparative Example 3 90% 8.9 882

[0069] It can be seen from Table 1 that the specific surface area of ​​the composite material obtained without adding the black spore algae powder is small, thereby reducing the adsorption performance of the material; the compressive performance of the composite material obtained without adding the black spore algae powder is also relatively poor.

[0070] The combustion performance of the composite materials of Examples 1 to 3 and Comparative Examples 1 to 3 was tested using a horizontal vertical combustion tester (in accordance with the US UL94 standard). The test results are shown in Table 2.

[0071] Table 2 Flame retardant performance test results of Examples 1 to 3 and Comparative Examples 1 to 3

[0072] Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Flame retardant 94V1 94V1 94V1 No flame retardancy 94V1 94V0

[0073] As can be seen from Table 2, the composite material without adding phytic acid has no flame retardancy, while the flame retardancy level of the composite material without adding silicon nitride is slightly lower.

[0074] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A highly flame-retardant honeycomb composite material, characterized in that: The composition comprises the following components in parts by weight: 40-50 parts of powdered activated carbon, 20-30 parts of modified black spore algae powder, 1-10 parts of phytic acid, 1-10 parts of binder, 1-5 parts of silicon nitride, 1-5 parts of sodium chloride, and 1-10 parts of water; The method for preparing the highly flame-retardant honeycomb composite material comprises the following steps: S1, calcining the black spore algae powder to obtain modified black spore algae powder; S2, mixing all the raw materials to form a mud material, and extruding it to obtain a honeycomb composite material embryo; S3, sequentially drying and activating the honeycomb composite material embryo to obtain a highly flame-retardant honeycomb composite material; In the step S1, the calcination temperature is 700-1000° C., and the calcination time is 30-60 min.

2. The highly flame-retardant honeycomb composite material according to claim 1, characterized in that: The particle size of the powdered activated carbon is ≤100 μm.

3. The highly flame-retardant honeycomb composite material according to claim 2, characterized in that: The particle size of the black spore algae powder is 30-100 meshes.

4. The highly flame-retardant honeycomb composite material according to claim 2 or 3, characterized in that: The binder is one or more of starch, dextrin, tar and polyvinyl alcohol.

5. The highly flame-retardant honeycomb composite material according to claim 4, characterized in that: The powdered activated carbon is coal-based activated carbon and / or fruit shell activated carbon.

6. The method for preparing the highly flame-retardant honeycomb composite material according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1, calcining the black spore algae powder to obtain modified black spore algae powder; S2, mixing all the raw materials to form a mud material, and extruding it to obtain a honeycomb composite material embryo; S3, sequentially drying and activating the honeycomb composite material embryo to obtain a highly flame-retardant honeycomb composite material; In the step S1, the calcination temperature is 700-1000° C., and the calcination time is 30-60 min.

7. The preparation method according to claim 6, characterized in that: In the step S2, the vacuum degree during extrusion is -0.05 to -0.1 MPa.

8. The preparation method according to claim 6 or 7, characterized in that: In step S3, the drying temperature is 100-200° C., and the drying time is 1-10 hours; the activation temperature is 500-600° C., and the activation time is 1-5 hours.

9. Use of the highly flame-retardant honeycomb composite material according to any one of claims 1 to 5 in the adsorption and purification treatment of VOCs waste gas.

Citation Information

Patent Citations

  • Preparation method of sargassum horneri matrix activated carbon

    CN103408011A

  • Preparation method of novel cellulose adsorbent

    CN104525138A